2004
DOI: 10.1016/s0006-3495(04)74244-7
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field-Driven Transformations of a Supported Model Biological Membrane—An Electrochemical and Neutron Reflectivity Study

Abstract: A mixed bilayer of cholesterol and dimyristoylphosphatidylcholine has been formed on a gold-coated block of quartz by fusion of small unilamellar vesicles. The formation of this bilayer lipid membrane on a conductive surface allowed us to study the influence of the support's surface charge on the structure and hydration of the bilayer lipid membrane. We have employed electrochemical measurements and the specular reflection of neutrons to measure the thickness and water content in the bilayer lipid membrane as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
192
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(218 citation statements)
references
References 55 publications
(60 reference statements)
24
192
2
Order By: Relevance
“…By performing slow potential scans when the electroactive liposome suspension is added to the electrochemical cell, it is possible to monitor the formation of the sensing layer. It has been reported that the structure of a lipid bilayer on a gold support changes according to the applied potential [31]. Slow scan rates allow the system to reach the equilibrium structure of the immobilized lipid layers at each potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By performing slow potential scans when the electroactive liposome suspension is added to the electrochemical cell, it is possible to monitor the formation of the sensing layer. It has been reported that the structure of a lipid bilayer on a gold support changes according to the applied potential [31]. Slow scan rates allow the system to reach the equilibrium structure of the immobilized lipid layers at each potential.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown by Burgess et al [31] that changes in potential cause changes in the structure of the lipid membrane close to the surface and in the water layer usually found in between the lipids and the gold surface. Therefore, the water content, thickness, density and viscosity of the bilayer in contact with the sensor vary constantly upon potential scanning.…”
Section: Formation and Characterization Of The Sensing Layermentioning
confidence: 99%
“…Defects are present in these bilayers and the hydrocarbon chains at phospholipid molecules adapt a large tilt with respect to the electrode surface [8,120]. In order to increase the molecular-scale order in phospholipid bilayers obtained by vesicles spreading addition of cholesterol is necessary [9,11,32,88,126]. Phospholipid molecules in bilayers prepared by LB-LS transfer are closer packed, uniformly oriented, and show a higher degree molecular-scale order than lipid molecules in bilayers prepared by vesicles spreading [9,31,33,120,127,128].…”
Section: Application Of In Situ Pm Irras For the Determination Of Thementioning
confidence: 99%
“…These systems can be used, e.g., as tools for the study of the properties of lipid membranes and how they are affected by the surrounding conditions (e.g., electric potential 1,2 , composition of the bulk solution 3 etc.). They are also of great interest as systems to study membrane-analyte interactions, including the study of peptide-and protein-membrane interactions 4,5 .…”
Section: Introductionmentioning
confidence: 99%